INTELLECTUAL CAPITAL, SOCIAL CAPITAL, PERENCANAAN DAN PENGEMBANGAN KARIER - fachrudy asjari (Fakultas Ekonomi Universitas PGRI Adi Buana, 2014)
Human Resources is a natural resource that is used to drive and synergizing other resources to achieve organizational goals. This research intended to analyze the intellectual capital, social capital, carrier and development planning. New intellectual capital was facilitated by social capital. Organizations as institutional settings conducive to the development of high level of social capital. This research by utilizing literature study to analyze variables. Carrier and development planning needs a few variables to support them get the goals. These variables in this study revealed that these variables needed by companies. The results of this research were empirical date of the development of the theoretical of human resources and practice management.